Antibiotic use in aquaculture, policies and regulation, health and environmental risks: a review of the top 15 major producers. (7th April 2019) - Lulijwa, Ronald; Rupia, Emmanuel Joseph; Alfaro, Andrea C.
Abstract: This review focuses on the current status of antibiotics use, effects on animal health and the environment, existing policies and regulatory mechanisms in the top 15 producing countries. Fifty papers were reviewed and represented the bulk of literature worldwide. We observed that 67 antibiotic compounds were used in 11 of the 15 countries between 2008 and 2018. Among these countries, 73% applied oxytetracycline, sulphadiazine and florfenicol. On average, countries used 15 antibiotics and the top users included Vietnam (39), China (33) and Bangladesh (21). On environmental and health risks, the review revealed sufficient evidence that directly links antibiotics use to food safety, occupational health hazards and antimicrobial resistance. Environmental risks included residue accumulation, aquatic biodiversity toxicity, microbial community selection for antibiotic resistance and the emergence of multi‐antibacterial resistant strains. Regarding policies, major players were the European Commission, the Food and Drug Administration, European Medicines Agency, Norwegian Veterinary Institute, the Norwegian Food Safety Authority, Codex and government ministries. In particular, the Norwegian Food Safety Authority and Norwegian Veterinary Institute demonstrated the most outstanding regulation mechanisms of antibiotics use in aquaculture that needs to be emulated. The future of aquaculture lies in guaranteeing the supply of safe aquatic products to the growing consumer market. Thus, international coordination of the policy and regulatory environment is needed, while increased investment in research for alternative aquatic health management strategies is essential. Future technologies should focus on the reduction of antibiotics use to safeguard the environment and ensure safety of consumers, feed industry and aquaculture workers.